Grass pollen allergoids conjugated with mannan for subcutaneous and sublingual immunotherapy: a dose-finding study - Ojeda, Pedro; Barjau, María Concepción; Subiza, Javier; Moreno, Antonio; Ojeda, Isabel; Solano, Emilio; Alonso, Alicia; Caballero, Raquel; Del Pozo, Sandra; Gómez-Perosanz, Marta; Sánchez-Trincado, José Luis; Benito-Villalvilla, Cristina; et al. (Frontiers in Immunology, 2024)
Background: Polymerized allergoids conjugated with mannan represent a novel approach of allergen immunotherapy targeting dendritic cells. In this study, we aimed to determine the optimal dose of mannan-allergoid conjugates derived from grass pollen (Phleum pratense and Dactylis glomerata) administered via either the subcutaneous or sublingual route.A randomized, double-blind, placebo-controlled trial with a double-dummy design was conducted, involving 162 participants across 12 centers in Spain. Subjects were randomly allocated to one of nine different treatment groups, each receiving either placebo or active treatment at doses of 500, 1,000, 3,000, or 5,000 mTU/mL over four months. Each participant received five subcutaneous (SC) doses of 0.5 mL each, every 30 days, and a daily sublingual (SL) dose of 0.2 mL. Participants who received active treatment through SC, received placebo through SL. Participants who received active treatment through SL, received placebo SC. One Group, as control, received bot SC and SL placebo. The primary efficacy outcome was the improvement in titrated nasal provocation tests (NPT) at the end of the study compared to baseline. Secondary outcomes included specific antibody (IgG4, IgE) and cellular (IL-10 producing and regulatory T cell) responses. All adverse events and side reactions were recorded and assessed.Results: Post-treatment, the active groups showed improvements in NPT ranging from 33% to 53%, with the highest doses showing the greatest improvements regardless of the administration route. In comparison, the placebo group showed a 12% improvement. Significant differences over placebo were observed at doses of 3,000 mTU/mL (p=0.049 for SL, p=0.015 for SC) and 5,000 mTU/mL (p=0.011 for SL, p=0.015 for SC). A dose-dependent increase in IgG4 was observed following SC administration, and an increase in IL-10 producing cells for both routes of administration. No serious systemic or local adverse reactions were recorded, and no adrenaline was required.Conclusions: Grass pollen immunotherapy with mannan-allergoid conjugates was found to be safe and efficacious in achieving the primary outcome, whether administered via the subcutaneous or sublingual routes, at doses of 3,000 and 5,000 mTU/mL.